"Hearing" Moism in Sandalwood Death: Mo Yan Thought as "the Spirit of Petty-Bourgeois Sentimentality and Social Fantasy". Issue 2 (2nd April 2016) - Xie, Jerry
ABSTRACT: Mo Yan's novel Sandalwood Death was translated into English in 2013 (from the 2001 novel Tanxiang Xing ) following the author's award of the Nobel Prize in Literature in 2012, at which time the term "hallucinatory realism" was invoked to describe his fiction. The novel was quickly hailed in the South China Morning Post (January 20, 2013) as "an orgy of pain and pleasure, " an "emotional see-saw" that is "chilling, but always human." This essay critically analyzes two major stylistic modes or narrative techniques elaborated throughout the novel: sounds or sound-effects such as the "meow" of a cat, and similarities––which I call "hypersimilarity"––in "hallucinatory" descriptions involving "as, " "as if" and "like." Moist (Mo-ist) narrative reflects a spontaneous poststructuralist apprehension of "reality" conveyed in "hallucinatory" or "spirited" illusions, most significantly in the practice of writing that Derrida called " freeplay ." Moism (Mo-ism) operates on an ideological level in the way that Marx called, in volume I of Capital, "a kind of Pied Piper of Hamelin": the central aim, under Mo Yan's banner of appealing to an "affinity" with the "common man, " is to demoralize and simultaneously remoralize readers as "playfully" docile, melancholic subjects of exploitation, dehumanization, hypocrisy, and cynical cleverness.